A diaphragm and its preparation method and application
By forming a layered bimetallic hydroxide three-dimensional framework on the separator and distributing polymer microspheres, the problem of difficulty in taking into account the breathability and adhesion of the existing separator is solved, and higher battery capacity and cycle stability are achieved.
Patent Information
- Application Number
- CN202411010717.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-07-26
AI Technical Summary
When the existing separators improve the interface adhesion with the electrode sheet, it is difficult to take into account both the breathable performance and the electrolyte wetting properties, resulting in limited battery capacity and cycle stability.
A three-dimensional framework formed by overlapping layered bimetal hydroxides and distribute polymer microspheres on them in a disorderly manner to form a composite coating layer to improve the adhesion and breathability of the separator.
Through the combined action of the three-dimensional framework and polymer microspheres, the interface adhesion between the separator and the electrode sheet is significantly improved, while maintaining good breathability and electrolyte wetting, thereby improving battery capacity and cycling stability.
Smart Images

Figure CN118712654B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a diaphragm and a preparation method and application thereof. Background Art
[0002] The global demand for diaphragms continues to grow, and the market is unprecedentedly huge. At present, in order to further improve the interface adhesion between the diaphragm and the pole piece and reduce the attenuation of the battery cell cycle capacity, the surface of the diaphragm is usually coated with organic materials to give it better pole piece adhesion, but the addition of polymer coating will reduce the air permeability.
[0003] Therefore, there is an urgent need to provide a diaphragm that has both air permeability and interface adhesion with the electrode. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a diaphragm and a preparation method and application thereof. In the diaphragm of the present invention, the coating layer includes a three-dimensional skeleton formed by overlapping layered double metal hydroxides, and polymer microspheres randomly distributed in the three-dimensional skeleton. Under the joint action of the three-dimensional skeleton and the polymer microspheres, the interfacial adhesion between the diaphragm and the pole piece can be improved, and the diaphragm has good air permeability and excellent electrolyte wettability, thereby helping to improve the battery capacity and cycle stability.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a diaphragm, the diaphragm comprising a base film, and a coating layer disposed on at least one side of the base film;
[0007] The coating layer comprises a three-dimensional framework formed by overlapping layered double metal hydroxides, and polymer microspheres randomly distributed in the three-dimensional framework.
[0008] Preferably, the layered double hydroxide has a layered porous structure.
[0009] In the present invention, on the basis of the layered double metal hydroxides overlapping each other to form a three-dimensional skeleton, the layered double metal hydroxides themselves also have a layered porous structure, which can further improve the air permeability of the diaphragm.
[0010] Preferably, the layered double metal hydroxide includes at least one of magnesium aluminum double metal hydroxide, lithium aluminum double metal hydroxide, zinc aluminum double metal hydroxide and nickel aluminum double metal hydroxide, preferably lithium aluminum double metal hydroxide.
[0011] A layered double hydroxide (LDH) is represented by [M 2+ 1-x M3+ x (OH)2] x+ A y- x / y nH2O, where M 2+ and M 3+ are metal divalent and metal trivalent cations, A y- Represents interlayer cations, such as magnesium aluminum double hydroxide, zinc aluminum double hydroxide or nickel aluminum double hydroxide, etc.
[0012] In addition to M 2+ / M 3+ In addition to the type of layered double hydroxides, there is another unique type of layered double hydroxide, namely lithium aluminum double hydroxide (LiAl-LDH), whose molecular formula is [LiAl2(OH)6] + A y- H2O, because lithium ion is an alkali metal cation that can be embedded in the LDH structure without damaging the LDH structure. In the LiAl-LDH structure, the cation Li + Located in the empty octahedral position of the Al(OH)3 layer, where Al 3+ Occupying 2 / 3 of the octahedral positions, they contribute to the positive charge of the hydroxide layer, so they have a higher anion exchange capacity. In addition, lithium aluminum double hydroxide is a chemical that can well guide lithium deposition. It has a special layered porous structure, which has abundant lithium ion diffusion pathways, good affinity for electrolytes and inhibition of lithium dendrites.
[0013] In summary, the present invention preferably uses lithium aluminum double metal hydroxide and polymer microspheres for combination, and the corresponding diaphragm is suitable for use in lithium ion batteries, which can improve the electrochemical performance of the battery. However, the corresponding diaphragms such as magnesium aluminum double metal hydroxide, zinc aluminum double metal hydroxide or nickel aluminum double metal hydroxide are used in lithium ion batteries, which may cause battery short circuit.
[0014] Preferably, the particle size D50 of the layered double hydroxide is 0.2-0.4 μm, for example, it can be any one of 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm or 0.4 μm, or a range between any two values.
[0015] Preferably, the average pore size of the layered double hydroxide is 3.0-4.5 nm, for example, it can be any one of 3.0 nm, 3.1 nm, 3.2 nm, 3.3 nm, 3.4 nm, 3.5 nm, 3.8 nm, 4 nm, 4.2 nm or 4.5 nm, or a range value between any two values.
[0016] Preferably, the specific surface area of the layered double hydroxide is 25 to 40 m 2 / g, for example, it can be 25m 2 / g, 26m 2 / g, 27m 2 / g, 28m 2 / g, 30m 2 / g, 32m 2 / g, 35m 2 / g, 38m 2 / g or 40m 2 / g, etc. or the range between any two values.
[0017] In the present invention, when the specific surface area of the layered double hydroxide is greater than 40 m 2 / g, the micropores on the surface of the layered double hydroxide particles are relatively few, which will have a certain impact on air permeability, which will affect the lithium ion transmission in the later stage, and the corresponding slurry viscosity is too large, which will lead to poor fluidity. The coating on the machine requires tedious debugging and process adjustment. If the viscosity is reduced by reducing the solid content of the slurry, it will affect the efficiency of the coating process. Low solid content of the slurry will cause abnormal points such as missing coating and uneven coating during the coating process, thereby affecting the performance of the diaphragm. When the specific surface area of the layered double hydroxide particles is less than 25m 2 / g, its own porous structure and the three-dimensional network structure formed by its own overlap make the diaphragm form too high porosity, thermal stability and mechanical properties deteriorate. Therefore, the specific surface area of layered double hydroxide is 25-40m 2 / g is most suitable.
[0018] In the present invention, the specific surface area of the layered double hydroxide is closely related to the pore size, particle size, coating slurry viscosity, and the corresponding membrane porosity, air permeability and thermal stability.
[0019] Preferably, the polymer microspheres include polyethylene wax microspheres and / or polyvinylidene fluoride (PVDF) microspheres.
[0020] Preferably, the polyethylene wax microspheres are of a core-shell structure, wherein the material of the core includes hydroxy polyethylene, and the material of the shell includes polyacrylate.
[0021] In the present invention, the polyethylene wax microspheres are core-shell structures, the polyacrylate shell provides high adhesion, and the hydroxy polyethylene core provides chemical stability. In addition to excellent electrode bonding performance, the polyethylene wax microspheres have a low swelling rate and are fluorine-free, meeting environmental protection and bonding performance requirements.
[0022] Preferably, the particle size D50 of the polyethylene wax microspheres is 0.8-1.2 μm, for example, it can be any one of 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, 1.05 μm, 1.1 μm, 1.15 μm or 1.2 μm, or a range value between any two values.
[0023] In the present invention, the particle size D50 of the polyethylene wax microspheres is greater than the particle size D50 of the layered double metal hydroxide, which results in more contact points between the polyethylene wax microspheres and the pole pieces, greatly improving the hot pressing bonding performance of the pole pieces of the diaphragm.
[0024] When the particle size D50 of the polyethylene wax microspheres is less than 0.8 μm, the particles of the polyethylene wax microspheres become smaller and are prone to clogging, resulting in a decrease in the porosity of the coating layer, affecting the air permeability index of the diaphragm. At the same time, the prepared slurry will be easily agglomerated, and as the storage time increases, the slurry will undergo soft and hard precipitation, and the slurry will lose fluidity as the viscosity of the slurry increases rapidly, making it impossible to load the machine. If water is added to dilute it until it can be loaded onto the machine, the process efficiency will be affected, and the coating film will be prone to surface defects such as uneven coating and missing coating. When the polyethylene wax microspheres D50 are greater than 1.2 μm, due to the increase in the size of the polyethylene wax microspheres D50, their contact specific surface area becomes smaller and smaller, and the bonding force with the electrode after hot pressing will be too small.
[0025] Preferably, the ratio of the particle size D50 of the polyethylene wax microspheres to the particle size D50 of the layered double hydroxide is 2 to 6, for example, it can be any one of 2, 3, 4, 5 or 6, etc., or a range value between any two values.
[0026] Preferably, the particle size D50 of the polyvinylidene fluoride microspheres is 0.2-0.5 μm, for example, it can be any one of 0.2 μm, 0.25 μm, 0.3 μm, 0.4 μm or 0.5 μm, or a range between any two values.
[0027] Preferably, the mass ratio of the polymer microspheres to the layered double hydroxide is (1-1.5):1, for example, it can be any one of 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, or a range value between any two values.
[0028] Preferably, a plurality of polymer microspheres are randomly distributed in the three-dimensional skeleton, and at least some of the polymer microspheres protrude from the surface of the three-dimensional skeleton, with the height of the protruding portion being 0.2-0.4 nm.
[0029] The term "multiple" in the present invention refers to at least 2, for example, any one of 2, 5, 10, 20, 50, 100, 200 or 500, or a range between any two values. At least part of the polymer microspheres protrude from the surface of the three-dimensional skeleton, including two situations: part of the polymer microspheres protrude from the surface of the three-dimensional skeleton or all of the polymer microspheres protrude from the surface of the three-dimensional skeleton.
[0030] Preferably, the coating layer further comprises a binder and a dispersant.
[0031] Preferably, the adhesive comprises any one of acrylic acid, polyacrylate or polyurethane, or a combination of at least two thereof.
[0032] Preferably, the dispersant comprises an anionic surfactant and / or a polymer dispersant.
[0033] Optionally, the anionic surfactant includes sulfates and / or alkylphenol polyoxyethylene ethers.
[0034] Optionally, the polymer dispersant comprises polyethylene glycol and / or polyvinyl ester.
[0035] Preferably, the height of the coating layer is 1-1.2 μm, for example, it can be any one of 1 μm, 1.05 μm, 1.1 μm, 1.15 μm or 1.2 μm, or a range between any two values.
[0036] Preferably, the bulk density of the coating layer is 1.2 to 1.5 g / cm 3 , for example, it can be 1.1 g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 Any one or the range between any two values.
[0037] Preferably, the porosity of the diaphragm is 40-55%, for example, it can be any one of 40%, 41%, 42%, 43%, 44%, 45%, 47%, 48%, 50%, 52% or 55%, etc., or a range value between any two values.
[0038] In a second aspect, the present invention provides a method for preparing the diaphragm according to the first aspect, the preparation method comprising:
[0039] (1) mixing a layered double metal hydroxide, a dispersion containing polymer microspheres, and a solvent to obtain a slurry;
[0040] (2) The slurry is applied to at least one surface of a base film to obtain the separator.
[0041] Preferably, the layered double metal hydroxide includes at least one of magnesium aluminum double metal hydroxide, lithium aluminum double metal hydroxide, zinc aluminum double metal hydroxide and nickel aluminum double metal hydroxide, preferably lithium aluminum double metal hydroxide.
[0042] Preferably, the solvent in step (1) comprises water.
[0043] Preferably, the preparation method of the lithium aluminum double hydroxide comprises: + and OH - The solution is mixed and hydrothermal reaction is carried out to obtain lithium aluminum double hydroxide.
[0044] In the traditional Bayer process, aluminum hydroxide / boehmite is placed in high-concentration sodium hydroxide at a high temperature of 270°C, and the resulting product is Bayer liquid. The tetrahedral aluminate ion Al(OH)4 - , lithium ions are embedded in it to form LiAl-LDH. The traditional Bayer process for preparing lithium aluminum double-layer hydroxide has harsh conditions, serious energy waste, slow reaction rate and is not easy to mass produce. The specific reaction process is as follows:
[0045]
[0046]
[0047]
[0048] The present invention uses metal Al and Li + and OH - The preparation reaction process of the solution as raw material is as follows:
[0049]
[0050]
[0051] From the above reaction equation, it can be seen that the present invention uses metal Al and Li + and OH - The solution reacts directly to form lithium aluminum double hydroxide.
[0052] The present invention uses metal Al and Li+ and OH -The preparation of lithium aluminum double hydroxide porous layered particles using solution as raw material has two advantages over the traditional Bayer process: ① First, the reaction process is a spontaneous reaction with a fast reaction speed, and does not require a specific high temperature to react, which can save energy accordingly, and is highly efficient and simple; ② The preparation reaction process is an exothermic process that produces hydrogen. The heat and hydrogen generated by the reaction can be converted into electrical energy, which can save energy while recovering energy, thus forming resource recycling.
[0053] Preferably, the particle size D50 of the metal Al is 0.1-0.3 μm, for example, it can be any one of 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm or 0.3 μm, or a range between any two values.
[0054] In the present invention, controlling the particle size of metal Al within a suitable range is helpful to form LiAl-LDH with a suitable particle size and specific surface area.
[0055] Preferably, the metal Al is obtained by mechanically milling aluminum foil.
[0056] Preferably, the temperature of the mechanical ball milling is controlled at 0-15° C., as oxidation reaction is likely to occur on the surface of the aluminum foil at a temperature exceeding 15° C.
[0057] Preferably, the Li-containing + and OH - The solution includes a LiOH solution, and the concentration of the LiOH solution is 1 to 5 mol / L, for example, it can be any one of 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, or a range value between any two values.
[0058] In the present invention, when the concentration of the LiOH solution is less than 1 mol / L, the solution concentration is insufficient to promote the reaction.
[0059] Preferably, the preparation process of the LiOH solution comprises: dissolving 2.4-12 kg of LiOH in 100 kg of water at 90-100° C. to obtain the LiOH solution.
[0060] Preferably, the Al element in the metal Al and the Li-containing + and OH - The molar ratio of the Li element in the solution is 0.1 to 2, for example, it can be any one of 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8 or 2, or a range between any two values.
[0061] In the present invention, when the Al / Li molar ratio is 0.1≤≤2, the product is mainly a large amount of LiAl-LDH and a small amount of aluminum oxide byproduct, and LiAl-LDH with high purity can be obtained. As the Al / Li molar ratio increases, aluminum oxide increases and the yield of LiAl-LDH decreases.
[0062] When the molar ratio of Al element to Li element is greater than 2, that is, the Al / Li molar ratio is greater than 2, most of the products are mainly by-products of gibbsite and diaspore, and the yield of LiAl-LDH product is too low. When it is used for coating lithium battery diaphragm in the later stage, the improvement of diaphragm thickness and air permeability is not obvious, which does not meet the use requirements.
[0063] When the Al / Li molar ratio is less than 0.1, only an aluminate solution can be formed, and no lithium aluminum double hydroxide is formed. The coated diaphragm prepared later cannot meet the air permeability requirements, so the slurry prepared from the product cannot be used for lithium battery diaphragm coating.
[0064] Preferably, the temperature of the hydrothermal reaction is 50-70°C, for example, it can be any one of 50°C, 55°C, 60°C, 65°C or 70°C, etc., or a range value between any two values, and the time of the hydrothermal reaction is 20-24h, for example, it can be any one of 20h, 21h, 22h, 23h or 24h, etc., or a range value between any two values.
[0065] Preferably, based on the mass of the slurry being 100%, the mass fraction of the layered double hydroxide is 4-6%, for example, it can be any one of 4%, 4.5%, 5%, 5.5% or 6%, etc., or a range value between any two values.
[0066] In the present invention, when the mass fraction of the layered double hydroxide is too large, the slurry viscosity will be too high, resulting in difficulty in coating; when the mass fraction of the layered double hydroxide is too small, the thermal stability and mechanical properties of the diaphragm are limited, and the air permeability deteriorates.
[0067] Preferably, the solid content of the dispersion containing polymer microspheres is 28-32%, for example, it can be any one of 28%, 29%, 30%, 31% or 32%, etc., or a range between any two values.
[0068] In the present invention, when the solid content of the dispersion containing polymer microspheres is too high, the dispersion has poor fluidity, is not easy to mix evenly with the layered double metal hydroxide during pulping, and is easy to agglomerate and stratify. When the solid content of the dispersion containing polymer microspheres is too low, the polymer microspheres are easy to settle and are easy to form hard precipitates after a long storage time.
[0069] Preferably, based on the mass of the slurry being 100%, the mass fraction of the polymer microspheres is 4-6%, for example, it may be any one of 4%, 4.5%, 5%, 5.5% or 6%, etc., or a range value between any two values.
[0070] In the present invention, when the mass fraction of polymer microspheres is greater than 6%, the viscosity of the slurry system will be too high and the fluidity will be poor, and multiple adjustments will be required during the coating process. At the same time, the excessive viscosity may lead to uneven distribution on the membrane surface; when the mass fraction of polymer microspheres is less than 4%, the bonding performance of the prepared diaphragm to the electrode is limited.
[0071] Preferably, a binder and a dispersant are also added during the mixing process in step (1).
[0072] Preferably, based on the mass of the slurry being 100%, the mass fraction of the binder is 5-7%, for example, it may be any one of 5%, 5.5%, 6%, 6.5% or 7%, etc., or a range value between any two values.
[0073] Preferably, based on the mass of the slurry being 100%, the mass fraction of the dispersant is 0.1-0.5%, for example, it may be any one of 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc., or a range value between any two values.
[0074] Preferably, the solid content of the slurry is 13-19%, for example, it can be any one of 13%, 14%, 15%, 16%, 17%, 18% or 19%, etc., or a range value between any two values.
[0075] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:
[0076] (I) Adding metal Al with a particle size D50 of 0.1 to 0.3 μm to Li + and OH - The solution is then subjected to hydrothermal reaction at 50-70°C for 20-24h, solid-liquid separation and washing are performed, and then dried at 60-70°C for 5-8h to obtain lithium aluminum double metal hydroxide;
[0077] Wherein, the Li-containing + and OH - The solution is a LiOH solution, the concentration of the LiOH solution is 1 to 5 mol / L; the molar ratio of the Al element in the metal Al to the Li element in the LiOH solution is 0.1 to 2; the lithium aluminum double hydroxide has a layered porous structure and a specific surface area of 25 to 40 m 2 / g, average pore size is 3.0-4.5nm, particle size D50 is 0.2-0.4μm;
[0078] (II) mixing the lithium aluminum double metal hydroxide, the dispersion containing polymer microspheres and the solvent at a rotation speed of 1800 to 2000 rpm for 2 to 3 hours, then adding a binder to the obtained mixed product, mixing at a rotation speed of 1000 to 1200 rpm for 1 to 2 hours, and then adding a dispersant, mixing at a rotation speed of 500 to 800 rpm for 0.5 to 2 hours to obtain a slurry; the solid content of the slurry is 13 to 19%;
[0079] The polymer microspheres include polyethylene wax microspheres, which are core-shell structures, wherein the material of the core includes hydroxy polyethylene, and the material of the shell includes polyacrylate; the particle size D50 of the polyethylene wax microspheres is 0.8 to 1.2 μm; the solid content of the dispersion containing the polymer microspheres is 28 to 32%; the mass ratio of the polymer microspheres to the lithium aluminum double hydroxide is (1 to 1.5):1; the binder includes any one of acrylic acid, polyacrylate or polyurethane or a combination of at least two thereof; the dispersant includes an anionic surfactant and / or a polymer dispersant;
[0080] (III) The slurry is coated on at least one side of the base film by a micro-concave roller coating method, and then dried at 60-70° C. to obtain the separator.
[0081] Preferably, the solid-liquid separation method in step (I) comprises filtration, and the mesh size of the filtration is 2000-3000 mesh.
[0082] In a third aspect, the present invention provides a battery, wherein the battery comprises the diaphragm described in the first aspect or the diaphragm prepared by the preparation method described in the second aspect.
[0083] The battery includes but is not limited to a lithium-ion battery.
[0084] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0085] Compared with the prior art, the present invention has the following beneficial effects:
[0086] The present invention provides a diaphragm, in which a three-dimensional skeleton formed by overlapping layered double metal hydroxides has a large porosity. Under the joint action of the three-dimensional skeleton and polymer microspheres, the interfacial adhesion between the diaphragm and the electrode can be improved, and the diaphragm can have good air permeability and excellent electrolyte wettability, thereby improving the battery capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 This is a schematic diagram of the structure of the diaphragm prepared in Example 1 of the present invention.
[0088] Figure 2 This is a SEM image of the diaphragm prepared in Example 1 of the present invention.
[0089] Figure 3 This is the SEM image of LiAl-LDH in Example 1 of the present invention.
[0090] Figure 4 Schematic diagram of the structure of polyethylene wax microspheres in Example 1 of the present invention.
[0091] Figure 5 This is the infrared spectrum of the polyethylene wax microspheres in Example 1 of the present invention.
[0092] Figure 6 Schematic diagram of the diaphragm and pole piece before and after hot pressing provided in an embodiment of the present invention.
[0093] Among them, 1-base film; 2-three-dimensional skeleton; 3-polymer microspheres; 4-active material; 5-current collector. DETAILED DESCRIPTION
[0094] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0095] Example 1
[0096] This embodiment provides a diaphragm, such as Figure 1 As shown, the diaphragm includes a base film 1 and a coating layer arranged on both sides of the base film 1, and the thickness of the coating layer on one side is 1 μm;
[0097] The base film 1 is a 7 μm thick PE film, the brand of which is SW807C, purchased from Shenzhen Xingyuan Material Technology Co., Ltd.; the coating layer includes a three-dimensional skeleton 2 formed by overlapping lithium aluminum double metal hydroxide (LiAl-LDH), and a plurality of polymer microspheres 3 randomly distributed in the three-dimensional skeleton 2, some of the polymer microspheres 3 protrude from the surface of the three-dimensional skeleton 2, and the height of the protruding part is 0.2-0.4 nm; LiAl-LDH has a layered porous structure with a specific surface area of 25m 2 / g, an average pore size of 4.5nm, and a particle size D50 of 0.4μm; the polymer microspheres 3 are specifically polyethylene wax microspheres, which have a core-shell structure, the material of the inner core is hydroxy polyethylene, and the material of the outer shell is polyacrylate; the particle size D50 of the polyethylene wax microspheres is 0.8μm, and the ratio of the particle size D50 of the polyethylene wax microspheres to that of LiAl-LDH is 2.0; the ratio of the total mass of the polyethylene wax microspheres to the mass of LiAl-LDH is 1:1; the binder is acrylic acid, and the dispersant is polysulfate.
[0098] This embodiment provides a method for preparing the above-mentioned diaphragm, and the preparation method comprises:
[0099] (1) 7.2 kg of LiOH was dissolved in 100 kg of deionized water at 90°C to prepare a 3 mol / L LiOH solution; metal Al powder with a particle size D50 of 0.3 μm was added to the LiOH solution, and the Al / Li element molar ratio was 1.0. The reaction generated a large amount of heat and hydrogen. The reaction time was 24 h. The obtained solid was filtered through a 3000 mesh filter, and the salt on the surface was washed with deionized water. The solid product was dried in an oven at 70°C for 8 h to obtain LiAl-LDH;
[0100] (2) mixing LiAl-LDH, a dispersion containing polyethylene wax microspheres and water at a rotation speed of 1200 rpm for 1 hour, wherein the polyethylene wax microspheres are core-shell structures, the core material includes hydroxy polyethylene, and the shell material includes polyacrylate; the particle size D50 of the polyethylene wax microspheres is 0.8 μm; the solid content of the dispersion containing polyethylene wax microspheres is 30%, and the solvent in the dispersion is water; the ratio of the mass of the polyethylene wax microspheres to the mass of LiAl-LDH is 1:1; and then 6% acrylic acid (based on the mass of the slurry as 100%) was added to the mixed product, and the mixture was mixed at a speed of 1000 rpm for 1 hour. Then, 0.1% polysulfate dispersant (based on the mass of the slurry as 100%) was added to the obtained mixed product, and the mixture was mixed at a speed of 600 rpm for 0.5 hour to obtain a slurry; based on the mass of the slurry as 100%, the mass fraction of LiAl-LDH in the slurry was 4.0%, the mass fraction of polyethylene wax microspheres was 5.0%, and the total solid content of the slurry was 15%;
[0101] (3) The slurry is coated onto both side surfaces of the base film 1 by a micro-concave roller coating method, and then dried at 65° C. to obtain the diaphragm.
[0102] Figure 2 The SEM image of the diaphragm prepared in this embodiment is shown. It can be seen from the SEM image that the lamellar structure of LiAl-LDH overlaps itself to form a three-dimensional network structure, thereby providing a certain porosity, while the spherical polyethylene wax microspheres are randomly arranged in the three-dimensional network skeleton structure overlapped by LiAl-LDH, and most of the polyethylene wax microspheres protrude from the surface of the three-dimensional skeleton, and a small number of polyethylene wax microspheres are embedded, which reduces the porosity to a certain extent, but the effect is not significant. Since the size of the polyethylene wax microspheres is larger than that of LiAl-LDH, there are more contact points with the pole piece, so the hot pressing bonding performance of the pole piece is greatly improved.
[0103] Figure 3The SEM image of LiAl-LDH in this embodiment is shown. It can be seen from the image that the LiAl-LDH wafers are in the form of polygonal sheets, which overlap each other to form a three-dimensional network structure.
[0104] Figure 4 The schematic diagram of the structure of the polyethylene wax microspheres in this embodiment is shown. As can be seen from the figure, the polyethylene wax microspheres are divided into an outer shell and an inner shell, the outer shell is a polyacrylate shell, and the inner shell is a hydroxy polyethylene core. The outer shell provides high adhesion and the inner core provides chemical stability.
[0105] Figure 5 The infrared spectrum of the polyethylene wax microspheres in this embodiment is shown. As can be seen from the figure, at 3500cm -1 The stretching vibration peak of hydroxyl group -OH appeared near 2420 cm -1 The stretching vibration peak of methylene-CH2 appeared near 1680 cm -1 The carbonyl -C=O stretching vibration peak appears nearby, which corresponds to Figure 4 Functional groups in the structure diagram of polyethylene wax microspheres.
[0106] Example 2
[0107] The difference between this embodiment and embodiment 1 is that the particle size D50 of the polyethylene wax microspheres is 1.2 μm, and the ratio of the particle size D50 of the polyethylene wax microspheres to that of the LiAl-LDH is 3.0.
[0108] The remaining parameters remain the same as those in Example 1.
[0109] Example 3
[0110] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.3 μm, the average pore size is 3.75 nm, and the specific surface area is 2 m 2 / g, and the ratio of the particle size D50 of polyethylene wax microspheres to that of LiAl-LDH is 2.67.
[0111] The remaining parameters remain the same as those in Example 1.
[0112] Example 4
[0113] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.3 μm, the average pore size is 3.75 nm, and the specific surface area is 32 m 2 / g, the particle size D50 of polyethylene wax microspheres is 1.2 μm, and the ratio of the particle size D50 of polyethylene wax microspheres to that of LiAl-LDH is 4.0.
[0114] The remaining parameters remain the same as those in Example 1.
[0115] Example 5
[0116] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.2 μm, the average pore size is 3.0 nm, and the specific surface area is 40 m 2 / g, and the ratio of the particle size D50 of polyethylene wax microspheres to LiAl-LDH is 4.0.
[0117] The remaining parameters remain the same as those in Example 1.
[0118] Example 6
[0119] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.2 μm, the average pore size is 3.0 nm, and the specific surface area is 40 m 2 / g, the particle size D50 of polyethylene wax microspheres is 1.2 μm, and the ratio of the particle size D50 of polyethylene wax microspheres to that of LiAl-LDH is 6.0.
[0120] The remaining parameters remain the same as those in Example 1.
[0121] Example 7
[0122] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.15 μm, the average pore size is 2.5 nm, and the specific surface area is 45 m 2 / g, and the ratio of the particle size D50 of polyethylene wax microspheres to that of LiAl-LDH is 5.33.
[0123] The remaining parameters remain the same as those in Example 1.
[0124] Example 8
[0125] The difference between this embodiment and embodiment 1 is that the particle size D50 of LiAl-LDH is 0.1 μm, the average pore size is 2.6 nm, and the specific surface area is 45 m 2 / g, and the ratio of the particle size D50 of polyethylene wax microspheres to LiAl-LDH is 8.0.
[0126] The remaining parameters remain the same as those in Example 1.
[0127] Example 9
[0128] The difference between this embodiment and embodiment 6 is that the particle size D50 of the polyethylene wax microspheres is 1.3 μm, and the ratio of the particle size D50 of the polyethylene wax microspheres to that of LiAl-LDH is 6.5; some of the polyethylene wax microspheres in the diaphragm protrude from the surface of the three-dimensional skeleton, and the height of the protruding part is 0.35 to 0.5 nm.
[0129] The remaining parameters remain the same as those in Example 6.
[0130] Example 10
[0131] The difference between this embodiment and embodiment 1 is that the particle size D50 of the polyethylene wax microspheres is 0.7 μm, and the ratio of the particle size D50 of the polyethylene wax microspheres to that of the LiAl-LDH is 1.75; the slurry is prepared. Part of the polyethylene wax microspheres in the diaphragm protrude from the surface of the three-dimensional skeleton, and the height of the protruding part is 0 to 0.27 nm and is not 0.
[0132] The remaining parameters remain the same as those in Example 1.
[0133] Embodiment 11
[0134] The difference between this embodiment and embodiment 1 is that the addition amount of metal Al powder is adjusted so that the Al / Li element molar ratio is 0.5.
[0135] The remaining parameters remain the same as those in Example 1.
[0136] Example 12
[0137] The difference between this embodiment and embodiment 1 is that the addition amount of metal Al powder is adjusted so that the Al / Li element molar ratio is 0.1.
[0138] The remaining parameters remain the same as those in Example 1.
[0139] Embodiment 13
[0140] The difference between this embodiment and embodiment 1 is that the amount of metal Al powder added is adjusted so that the Al / Li element molar ratio is 2.
[0141] The remaining parameters remain the same as those in Example 1.
[0142] Embodiment 14
[0143] The difference between this embodiment and embodiment 1 is that the preparation method of the LiAl-LDH particles comprises:
[0144] Alumina is placed in a sodium hydroxide solution, the reaction temperature is 275°C, the reaction time is 5 hours, wherein the molar ratio of aluminum oxide to sodium hydroxide solid is 3:1, wherein the concentration of the sodium hydroxide solution is greater than 98.0%; after multiple washing, filtering and drying, NaAl(OH)4 particles are obtained; NaAl(OH)4 particles are placed in a LiOH solution and reacted for 30 hours, the reaction will generate a large amount of heat and hydrogen, and after multiple washing, filtering and drying, LiAl-LDH particles are obtained. The remaining parameters are consistent with Example 1.
[0145] Embodiment 15
[0146] The difference between this embodiment and embodiment 1 is that in step (2), the mass fraction of polyethylene wax microspheres in the slurry is adjusted to 2.0%. The other parameters are the same as those in embodiment 1.
[0147] Example 16
[0148] The difference between this embodiment and embodiment 1 is that in step (2), the mass fraction of LiAl-LDH in the slurry is adjusted to 6%, and the other parameters are consistent with those in embodiment 1.
[0149] Embodiment 17
[0150] The difference between this embodiment and embodiment 1 is that in step (2), the mass fraction of LiAl-LDH in the slurry is adjusted to 2%, and the other parameters are consistent with those in embodiment 1.
[0151] Embodiment 18
[0152] The difference between this embodiment and embodiment 1 is that the polyethylene wax microspheres are replaced with PVDF microspheres with a particle size D50 of 0.35 μm.
[0153] The remaining parameters remain the same as those in Example 1.
[0154] Embodiment 19
[0155] The difference between this embodiment and embodiment 1 is that the mass ratio of polyethylene wax microspheres to LiAl-LDH is 1.5:1.
[0156] The remaining parameters remain the same as those in Example 1.
[0157] Embodiment 20
[0158] The difference between this embodiment and embodiment 1 is that the mass ratio of polyethylene wax microspheres to LiAl-LDH is 1.8:1.
[0159] The remaining parameters remain the same as those in Example 1.
[0160] Comparative Example 1
[0161] This comparative example provides a boehmite@polyethylene wax microsphere mixed coating film, and its preparation method is different from that of Example 1 in that step (1) in the preparation method is omitted, and the LiAl-LDH in step (2) is replaced by boehmite (particle size D50 is 1 μm), and the other parameters are consistent with Example 1.
[0162] Comparative Example 2
[0163] This comparative example provides a pure LiAl-LDH coated diaphragm, and its preparation method is different from that of Example 1 in that the polyethylene wax microspheres in the slurry are omitted, and the remaining steps and parameters are consistent with those of Example 1. The pure LiAl-LDH coated diaphragm has a LiAl-LDH coating layer on both sides of the base film.
[0164] Performance Testing
[0165] The following tests were performed on the diaphragms provided in the above embodiments and comparative examples:
[0166] (1) Air permeability test:
[0167] ① Test the diaphragm porosity according to GB / T36363-2018;
[0168] ② Test the membrane air permeability value according to GB / T36363-2018.
[0169] (2) Bulk density test of coating layer:
[0170] Bulk density test according to GB / T-36363-2018;
[0171] (3) Heat shrinkage test:
[0172] With reference to GB / T12027-2004, the separators were placed in a forced air oven at 180°C for heat treatment for 60 minutes to perform a heat shrinkage test, and the thermal stability of the separator was evaluated by the heat shrinkage test.
[0173] (4) Adhesion test:
[0174] The long strips of diaphragms were respectively attached to the positive electrode sheet and the negative electrode sheet, and then placed on a hot press for hot pressing bonding. The positive electrode sheet was a lithium iron phosphate electrode sheet, and the negative electrode sheet was a graphite electrode sheet. The specific hot pressing parameters were: hot pressing temperature 90°C, hot pressing time 60s, and hot pressing pressure 6.5MPa. After that, the hot-pressed film was placed on a stretching machine for a peeling test (at a rate of 200mm / min), and the bonding strength values between the diaphragm and the positive electrode sheet and between the diaphragm and the negative electrode sheet were recorded respectively.
[0175] The positive and negative electrodes both include a current collector 5 and an active material 4 disposed on the surface of the current collector 5, such as Figure 6 As shown, under hot pressing conditions, the polymer microspheres 3 in the diaphragm of the present invention will soften and deform, and the polymer microspheres 3 monomers will be riveted to the interfaces of the positive and negative electrode sheets. After the hot pressing is completed, the polymer microspheres 3 harden to become an intermediate connecting the base film 1 and the active material 4. The mechanical riveting effect and the van der Waals force at the interface of the polymer microspheres 3 and the electrode sheets together give good interface bonding properties.
[0176] (5) Contact angle test:
[0177] The contact angle test is carried out according to GB / T30447-2018. The wettability of the diaphragm is judged by the contact angle.
[0178] The test results are shown in Table 1. Among them, in the values of the positive and negative electrode bonding strength, the left side is the bonding strength between the separator and the positive electrode, and the right side is the bonding strength between the separator and the negative electrode.
[0179] Table 1
[0180]
[0181] analyze:
[0182] It can be seen from the examples that in the coating layer of the diaphragm provided by the present invention, LiAl-LDH overlaps each other to form a three-dimensional skeleton, and the three-dimensional skeleton has a large porosity, so that the diaphragm has good air permeability and a suitable coating layer packing density, and the three-dimensional skeleton structure is conducive to the absorption of the electrolyte, so that the diaphragm obtains a smaller contact angle, that is, the diaphragm has excellent electrolyte wettability, and at the same time, the three-dimensional skeleton structure formed by LiAl-LDH makes the diaphragm have good thermal stability and low heat shrinkage; in addition, since LiAl-LDH overlaps each other to form a mesh structure with certain pores, the polyethylene wax microspheres will be embedded in the skeleton structure formed by LiAl-LDH due to their relatively large size and spherical special structure, so that they have better contact sites, thereby indirectly compensating for the defect of low bonding force between the positive and negative electrodes of the polyethylene wax microspheres with small specific surface area, so that the diaphragm has relatively good bonding performance. In summary, the diaphragm provided by the present invention has excellent comprehensive performance.
[0183] From Example 1 to Example 6, as the particle size D50 of LiAl-LDH decreases (specific surface area increases), the permeability value shows an upward trend in the range of 0.2 to 0.4 μm; however, as the particle size decreases and is compounded with polyethylene wax microspheres, the positive and negative electrode bonding forces show an upward trend, which may be due to the gradual increase in the specific surface area of LiAl-LDH and the formation of a better bonding force with the polyethylene wax microspheres.
[0184] It can be seen from Examples 1 and 7 that the particle size D50 of the lithium aluminum double hydroxide in Example 7 is too small, but meets the particle size ratio range of polyethylene wax microspheres and LiAl-LDH. Compared with Example 1, the air permeability, thermal stability and bonding properties of the diaphragm of Example 7 are deteriorated.
[0185] It can be seen from Examples 1 and 8 that the particle size D50 of the lithium aluminum double hydroxide in Example 8 is too small and the particle size ratio of the polyethylene wax microspheres to LiAl-LDH is too large. Compared with Example 1, the air permeability, adhesion and electrolyte wettability of the diaphragm of Example 8 are deteriorated.
[0186] It can be seen from Examples 1 and 9-10 that when the particle size D50 of the polyethylene wax microspheres is too large, the particle size ratio of the polyethylene wax microspheres to the lithium aluminum double metal hydroxide is also too large, and the height of the protruding part of the microspheres is relatively large, resulting in poor air permeability, bonding performance and electrolyte wettability of the diaphragm, wherein the poor bonding performance is due to the fact that as the size of the polyethylene wax microspheres increases, the contact specific surface area becomes smaller and smaller, and the bonding force with the pole piece after hot pressing becomes smaller and smaller; when the particle size D50 of the polyethylene wax microspheres is too small, the particle size ratio of the polyethylene wax microspheres to the lithium aluminum double metal hydroxide is also too small, and the height of the protruding part of the microspheres is relatively small, resulting in poor air permeability of the diaphragm, and decreased bonding performance and electrolyte wettability. Therefore, it is determined that the ratio of the particle size D50 of the polyethylene wax microspheres to the LiAl-LDH is between 2 and 6, which can meet the performance index requirements of the diaphragm.
[0187] It can be seen from Example 1 and Examples 11-13 that when 0.1≤Al / Li≤2, the product is mainly a small amount of aluminum oxide and a large amount of LiAl-LDH, and a high-purity LiAl-LDH can be obtained, which makes the diaphragm have excellent thermal stability. With the further increase of the concentration ratio, the aluminum oxide product will also increase, the yield will decrease, but the air permeability and electrolyte wettability of the diaphragm will be improved.
[0188] It can be seen from Example 1 and Example 14 that the LiAl-LDH particles prepared by the traditional Bayer process have an unclear pore structure due to process differences, so that the pore structure formed after overlapping each other is relatively small, and the air permeability, adhesion performance and electrolyte wettability of the corresponding diaphragm are all reduced.
[0189] It can be seen from Example 1 and Example 15 that in the process of preparing the diaphragm, if the mass fraction of the polyethylene wax microspheres in the slurry is too low, the air permeability and bonding properties of the diaphragm will be reduced.
[0190] It can be seen from Examples 1 and 16-17 that in the process of preparing the diaphragm, if the mass fraction of LiAl-LDH in the slurry is too low, the air permeability, thermal stability, adhesion and electrolyte wettability of the diaphragm will deteriorate.
[0191] As can be seen from Example 18, in the coating layer of the diaphragm provided by the present invention, LiAl-LDH overlaps each other to form a three-dimensional skeleton, and PVDF microspheres are randomly distributed in the three-dimensional skeleton. The diaphragm exhibits good comprehensive performance such as air permeability, bulk density, thermal stability, bonding performance and electrolyte wettability. Comparing Example 1 and Example 18, it is found that the diaphragm using polyethylene wax microspheres has better comprehensive performance, especially the positive and negative electrode bonding force of the diaphragm using polyethylene wax microspheres is greater than that of the diaphragm using PVDF microspheres. This is mainly because the polypropionate on the surface of the shell structure in the core-shell structure of the polyethylene wax microspheres gives the microspheres stronger bonding properties. Under hot pressing conditions, the polyethylene wax microspheres soften and deform, and the microsphere monomers are riveted to the positive and negative electrode interfaces, and their mechanical riveting force and van der Waals force together give good interfacial bonding force.
[0192] It can be seen from Examples 1 and 19-20 that when the mass ratio of polymer microspheres to lithium aluminum double hydroxide is too large, the membrane permeability and electrolyte wettability are reduced; when the mass ratio of polymer microspheres to lithium aluminum double hydroxide is too large, the membrane permeability, thermal stability and electrolyte wettability are significantly reduced.
[0193] From the comparison between Example 1 and Comparative Example 1, it can be seen that the boehmite@polyethylene wax microsphere mixed coated diaphragm provided in Comparative Example 1 is made of boehmite (AlOOH) as a ceramic material, mixed and coated with polyethylene wax microspheres; compared with the diaphragm provided in Example 1, the air permeability, thermal stability, and electrolyte wettability of the diaphragm of Comparative Example 1 are all deteriorated.
[0194] From the comparison between Example 1 and Comparative Example 2, it can be seen that Comparative Example 2 is a pure LiAl-LDH coated diaphragm without the participation of polyethylene wax microspheres. Compared with the diaphragm provided in Example 1, the air permeability and bonding properties of the diaphragm of this comparative example are reduced.
[0195] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A diaphragm, characterized in that: The diaphragm includes a base film and a coating layer disposed on at least one side of the base film; The coating layer includes a three-dimensional framework formed by overlapping layered double metal hydroxides, and polymer microspheres randomly distributed in the three-dimensional framework; The particle size D50 of the layered double metal hydroxide is 0.2-0.4 μm, the average pore size is 3.0-4.5 nm, and the specific surface area is 25-40 m 2 / g; The polymer microspheres include polyethylene wax microspheres; The ratio of the particle size D50 of the polyethylene wax microspheres to the particle size D50 of the layered double hydroxide is 2-6.
2. The diaphragm according to claim 1, characterized in that The layered double metal hydroxide has a layered porous structure.
3. The diaphragm according to claim 1, characterized in that The layered double metal hydroxide includes at least one of magnesium aluminum double metal hydroxide, lithium aluminum double metal hydroxide, zinc aluminum double metal hydroxide and nickel aluminum double metal hydroxide.
4. The diaphragm according to claim 3, characterized in that The layered double metal hydroxide is lithium aluminum double metal hydroxide.
5. The diaphragm according to claim 1, characterized in that The polyethylene wax microspheres are of a core-shell structure, wherein the material of the core comprises hydroxy polyethylene, and the material of the shell comprises polyacrylate.
6. The diaphragm according to claim 1, characterized in that The particle size D50 of the polyethylene wax microspheres is 0.8-1.2 μm.
7. The diaphragm according to claim 1, characterized in that The mass ratio of the polymer microspheres to the layered double metal hydroxide is (1-1.5):
1.
8. The diaphragm according to claim 1, characterized in that A plurality of polymer microspheres are randomly distributed in the three-dimensional skeleton, and at least some of the polymer microspheres protrude from the surface of the three-dimensional skeleton, with the height of the protruding portion being 0.2-0.4 nm.
9. The diaphragm according to claim 1, characterized in that The coating layer also includes a binder and a dispersant.
10. The diaphragm according to claim 9, characterized in that The binder includes any one of acrylic acid, polyacrylate or polyurethane, or a combination of at least two of them.
11. The diaphragm according to claim 9, characterized in that The dispersant includes an anionic surfactant and / or a polymer dispersant.
12. The diaphragm according to claim 1, characterized in that The coating layer has a thickness of 1-1.2 μm.
13. The diaphragm according to claim 1, characterized in that The bulk density of the coating layer is 1.2-1.5 g / cm 3 .
14. The diaphragm according to claim 1, characterized in that The porosity of the diaphragm is 40-55%.
15. A method for preparing a diaphragm according to any one of claims 1 to 14, characterized in that: The preparation method comprises: (1) mixing a layered double metal hydroxide, a dispersion containing polymer microspheres, and a solvent to obtain a slurry; (2) The slurry is applied onto at least one surface of a base film to obtain the separator.
16. The preparation method according to claim 15, characterized in that: The layered double metal hydroxide includes at least one of magnesium aluminum double metal hydroxide, lithium aluminum double metal hydroxide, zinc aluminum double metal hydroxide and nickel aluminum double metal hydroxide.
17. The preparation method according to claim 16, characterized in that: The layered double metal hydroxide is lithium aluminum double metal hydroxide.
18. The preparation method according to claim 17, characterized in that: The preparation method of the lithium aluminum double metal hydroxide comprises: + and OH - The solution is mixed and hydrothermal reaction is carried out to obtain lithium aluminum double hydroxide.
19. The preparation method according to claim 18, characterized in that: The particle size D50 of the metal Al is 0.1-0.3 mm.
20. The preparation method according to claim 18, characterized in that: The Li-containing + and OH - The solution includes a LiOH solution, and the concentration of the LiOH solution is 1-5 mol / L.
21. The preparation method according to claim 18, characterized in that: The Al element in the metal Al and the Li-containing + and OH - The molar ratio of Li element in the solution is 0.1~2.
22. The preparation method according to claim 18, characterized in that: The temperature of the hydrothermal reaction is 50-70° C., and the time of the hydrothermal reaction is 20-24 hours.
23. The preparation method according to claim 15, characterized in that: Based on the mass of the slurry being 100%, the mass fraction of the layered double metal hydroxide is 4-6%.
24. The preparation method according to claim 15, characterized in that: The solid content of the dispersion containing polymer microspheres is 28-32%.
25. The preparation method according to claim 15, characterized in that: Taking the mass of the slurry as 100%, the mass fraction of the polymer microspheres is 4-6%.
26. The preparation method according to claim 15, characterized in that: During the mixing process of step (1), a binder and a dispersant are also added.
27. The preparation method according to claim 26, characterized in that: Taking the mass of the slurry as 100%, the mass fraction of the binder is 5-7%.
28. The preparation method according to claim 26, characterized in that: Taking the mass of the slurry as 100%, the mass fraction of the dispersant is 0.1-0.5%.
29. The preparation method according to claim 15, characterized in that: The solid content of the slurry is 13-19%.
30. The preparation method according to claim 15, characterized in that: The preparation method specifically comprises the following steps: (I) Adding metal Al with a particle size D50 of 0.1~0.3mm to Li + and OH - The solution is then subjected to hydrothermal reaction at 50-70°C for 20-24h, and after solid-liquid separation and washing, it is dried at 60-70°C for 5-8h to obtain lithium aluminum double hydroxide; Wherein, the Li-containing + and OH - The solution is a LiOH solution, the concentration of the LiOH solution is 1-5 mol / L; the molar ratio of the Al element in the metal Al to the Li element in the LiOH solution is 0.1-2; the lithium aluminum double hydroxide has a layered porous structure and a specific surface area of 25-40 m 2 / g, average pore size is 3.0~4.5nm, particle size D50 is 0.2~0.4μm; (II) mixing the lithium aluminum double hydroxide, the dispersion containing polymer microspheres and the solvent at a rotation speed of 1800-2000 rpm for 2-3 hours, then adding a binder to the obtained mixed product, mixing at a rotation speed of 1000-1200 rpm for 1-2 hours, and then adding a dispersant, mixing at a rotation speed of 500-800 rpm for 0.5-2 hours to obtain a slurry; The polymer microspheres include polyethylene wax microspheres, which are core-shell structures, wherein the material of the core includes hydroxy polyethylene, and the material of the shell includes polyacrylate; the particle size D50 of the polyethylene wax microspheres is 0.8-1.2 μm; the solid content of the dispersion containing the polymer microspheres is 28-32%; the mass ratio of the polymer microspheres to the lithium aluminum double hydroxide is (1-1.5):1; the binder includes any one of acrylic acid, polyacrylate or polyurethane or a combination of at least two; the dispersant includes an anionic surfactant and / or a polymer dispersant; the solid content of the slurry is 13-19%; (III) The slurry is coated on at least one side of the base film by a micro-concave roller coating method, and then dried at 60-70° C. to obtain the separator.
31. A battery, characterized in that: The battery comprises the diaphragm according to any one of claims 1 to 14 or the diaphragm prepared by the preparation method according to any one of claims 15 to 30.
Citation Information
Patent Citations
Separators with layered double hydroxides for electrochemical cells
CN114008831A
Diaphragm and preparation method thereof, preparation method of double-metal hydroxide, electrode assembly, battery and electric equipment
CN118299761A
Coated diaphragm and preparation method therefor
WO2023123751A1